The Impact of Electronic Procurement (E-Procurement) on Public Sector Accountability in Ghana - Alhassan Musah; Adu Peprah James; Matilda Asiedu-Ampomah; Felicia Koomson (Journal of Governance and Accountability Studies, 2025)
Purpose: This study investigates the antecedents and consequences of e-procurement in Ghana, focusing on its role in enhancing transparency and accountability in public procurement. Methodology: The research surveyed 200 respondents from various government agencies in Accra, including the Department of Roads, Ghana Cocoa Board, Ghana Health Service, and Tema Metropolitan Assembly. ata were analyzed using descriptive statistics, chi-squared tests, simple regression analysis, and visual tools such as graphs and tables. Results: The findings revealed that the effective implementation of e-procurement in Ghana began in 2019, with agencies such as the Department of Feeder Roads, Ghana Cocoa Board, Ghana Health Service, Koforidua Technical University, and Tema Metropolitan Assembly adopting the system. The Ghana E-Procurement System (GHANEPS) includes key components such as e-tendering, e-requisition, e-tender evaluation, e-supplier selection, and e-supplier relationship management. The study also found that transparency, accountability, automation, and a secure system were critical success factors in reducing corruption. In addition, a positive association was observed between e-procurement adoption and transparency in public procurement. Conclusions: The findings underscore the significant role of e-procurement in enhancing transparency and accountability in Ghana’s public procurement processes. Limitations: The study was limited to selected government agencies in Accra, which may restrict the generalizability of the findings to other regions and institutions in Ghana. Contributions: This research contributes to the literature on public procurement reforms in Ghana, shedding light on the effectiveness of e-procurement in enhancing transparency and accountability topics that have not been extensively explored in the context of Ghanaian public procurement.